Comparison of cold water immersion protocols in female handball players after match training - Sánchez-Ureña, B.; Martinez-Guardado, I.; Espinoza-Acuña, G.; Camacho-Cardeñosa, M.; Camacho-Cardeñosa, A.; Timón, R.; Olcina, G. (Journal of Human Sport & Exercise, 2018)
Purpose: Compare the effect of two protocols cold water immersion on indicators of recovery in female handball players. Methods: 12 female handball players (Age: 14 ± 0.7 years, body mass: 58.44 ± 7.8 kg, Height: 161± 7.1 cm, fat %: 21.5± 3) were involved in a "cross-over" experimental design. After three training sessions (Avg heart rate 183 ± 9, 180 ± 8 and 180 ± 8b/pm respectively), participants were placed a continuous cold water immersion protocol (n=12), (12 min water temperature 14± 0.5C°), intermittent cold water immersion protocol (n=11), (4 x 2 min water temperature 14 ± 0.5C° + 1min out of water ) and control group (CG) with passive recovery (n=9). Countermovement jump test (CMJ), Visual Analog Scale (VAS-Pain) and thigh volume were measured. Results: Both cold water immersion protocols were effective in reducing the pain immediately post immersion, 24 and 48 hours after training compared with the CG (F(4,116) = 6.84, p < 0.001. ?p²: 0.32). CMJ (F(4,116) = 1,79, p =.11, ?p²: 0.02) and thigh volume (F(4,116) = 0.77, p =.59, ?p²: -0.007) did not report statistically significant changes at any time of measurement. Conclusions: Both CWI protocols are effective to reduce delayed on set muscle soreness at all times post training in female handball players. CWI should be included after training sessions to enhance players` recovery for the next training day. CWI protocol could be used according to individual preferences due to both of them have same effect in psychological indicators of recovery.